Modern Approaches to Formation of Digital Infrastructure - Yu. I. Gribanov; M. N. Rudenko; K. A. Alenina (Управленческое консультирование)
The concept of digital infrastructure is rather new and was widely adopted together with distribution of digital technologies and expansions of their functions in social and economic system. The concept of digital infrastructure is closely connected with concepts of information infrastructure and infrastructure of information technologies or information and communication technologies. The last, in turn, relate to a concept of information society. Info-communication technologies and networks modify social interrelations, new technologies create new communities which mainly arise and function on the network principle. Info-communication networks form new tools for interaction.